KEBIJAKAN PENDIDIKAN KARAKTER MELALUI PROFIL PELAJAR PANCASILA DALAM KONTEKS PERUBAHAN SOSIAL: LITERATURE REVIEW - Mahfud, Moh (IDEALITA: Jurnal Pendidikan dan Sosial Keagamaan, 2023)
This research aims to conduct a literature review on the profile of Pancasila learners and character education and their relationship with social change. The research method chosen for this study is Systematic Literature Review (SLR). Data collection was carried out by documenting and reviewing articles that examined "the profile of Pancasila learners," "character education," and "social change" published between 2018 and 2022. A total of 30 accredited national journal articles were used in this study, obtained from the Google Scholar database using the Publish or Perish application. Based on this research, it was found that the purpose of character education policy through the profile of Pancasila learners in the free curriculum context of social change also supports the achievement of national education goals. Furthermore, the continuation of character strengthening programs aims to produce graduates who are globally competitive, possess strong character, uphold the values of Pancasila in their hearts, and have personal resilience that impacts family resilience, community resilience, regional resilience, and national resilience, all while upholding the noble values and morals of the nation through 11 strategies.